2013
DOI: 10.1038/cddis.2013.62
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral movement training promotes axonal remodeling of the corticospinal tract and recovery of motor function following traumatic brain injury in mice

Abstract: Traumatic brain injury (TBI) results in severe motor function impairment, and subsequent recovery is often incomplete. Rehabilitative training is considered to promote restoration of the injured neural network, thus facilitating functional recovery. However, no studies have assessed the effect of such trainings in the context of neural rewiring. Here, we investigated the effects of two types of rehabilitative training on corticospinal tract (CST) plasticity and motor recovery in mice. We injured the unilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 52 publications
1
30
0
Order By: Relevance
“…5), suggesting that the increased mEPSC frequency is due instead to increased afferents onto these intact pyramidal neurons. Axonal sprouting has previously been observed in response to TBI 30,35,36 and axotomy. 37-40 It is unclear why a delay to sprouting onto these cells occurs.…”
Section: Journal Of Neurotraumamentioning
confidence: 95%
“…5), suggesting that the increased mEPSC frequency is due instead to increased afferents onto these intact pyramidal neurons. Axonal sprouting has previously been observed in response to TBI 30,35,36 and axotomy. 37-40 It is unclear why a delay to sprouting onto these cells occurs.…”
Section: Journal Of Neurotraumamentioning
confidence: 95%
“…Vicariation, or substitution of lost function by the residual network, would dominate in patients with more severe damage [ 24 ], suggesting a greater restorative effect of neural network remodeling in more severely affected individuals. Interestingly, general functional improvement was induced by skilled forelimb reach training only when training enhanced axonal remodeling in the corticospinal tract from the contralesional hemisphere; Starkey et al [ 21 ] reported enhanced axonal remodeling but we [ 15 ] and Nakagawa et al [ 22 ] did not observe a significant effect in the corticospinal tract from the contralesional hemisphere. Therefore, the extent of the brain area in which training induces axonal plasticity may be a deciding factor in the translatability of rehabilitation-induced functional recovery.…”
Section: Discussionmentioning
confidence: 63%
“…The translatability of the functional recovery induced by the skilled forelimb task differs between experiment settings. For example, Starkey et al reported that skilled forelimb reach training (50 successful attempts, 5 days per week for 6 weeks) after unilateral pyramidotomy led to an improved success rate in the horizontal ladder walk and the staircase task [ 21 ], while Nakagawa et al reported that skilled forelimb reach training (60 attempts, 6 days per week for 4 weeks) after traumatic brain injury improved the success rate only in the skilled forelimb reaching test but not in the staircase test, ladder walk test, or Capellini handling test [ 22 ]. These differences may be a result of the intensity of the training or the severity and type of injury.…”
Section: Discussionmentioning
confidence: 99%
“…Axonal remodeling is accepted as one of the components of TST-induced functional recovery and has been detected in parts of the CST [ 7 ]. Several studies of the beneficial effect of TST on functional recovery after injury have reported that rehabilitative training induces the growth of saved CST axons and the projection of new axons into the damaged spinal cord, subsequently contributing to motor recovery [ 8 , 29 , 38 , 39 ]. Our previous research demonstrated that early TST after stroke enhanced the contralesional plasticity of the CSTs in motor cortical and sensorimotor cortical lesions at the acute stage after stroke [ 5 ].…”
Section: Discussionmentioning
confidence: 99%